2017
DOI: 10.1507/endocrj.ej16-0429
|View full text |Cite
|
Sign up to set email alerts
|

Self-management in adrenal insufficiency — towards a better understanding

Abstract: CORTISOL is an essential stress hormone produced by the adrenal glands and tightly regulated via the hypothalamic-pituitary-adrenal axis. Cortisol deficiency is a rare, but life-threatening condition, requiring immediate diagnosis and treatment. The most common cause of primary adrenal insufficiency (AI) is an autoimmune process [1], but also infections, tissue infiltration, drugs or surgery may lead to insufficient production of glucocorticoids (GC) in the adrenal glands [2]. Secondary and tertiary AI are mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…[1] The role of the patient in recognizing when an increase in glucocorticoid doses is required is central to minimize the risk to themselves; thus, the importance of patient education is repeatedly emphasized. [2,3] Published existing literature has identified deficiencies in the patients' understanding of steroid sick day rules, [2,4] how to administer parenteral hydrocortisone, [2,4,5] and when to seek medical attention. [2] However, reports highlight gaps in clinician knowledge, particularly on the recognition, and the management of AI.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The role of the patient in recognizing when an increase in glucocorticoid doses is required is central to minimize the risk to themselves; thus, the importance of patient education is repeatedly emphasized. [2,3] Published existing literature has identified deficiencies in the patients' understanding of steroid sick day rules, [2,4] how to administer parenteral hydrocortisone, [2,4,5] and when to seek medical attention. [2] However, reports highlight gaps in clinician knowledge, particularly on the recognition, and the management of AI.…”
Section: Commentarymentioning
confidence: 99%
“…[2] However, reports highlight gaps in clinician knowledge, particularly on the recognition, and the management of AI. [4,[6][7][8] Given that healthcare professionals have a central role in patient education, it is essential that clinicians, irrespective of grade are familiar with steroid sick day rules and pharmacokinetics to avoid preventable adverse patient outcomes. Furthermore, the increasing use of drugs such as immune checkpoint inhibitors and the endocrinopathy side effects associated with these further supports the need for all physicians, not just endocrinologists, to recognize, and promptly initiate treatment AI.…”
Section: Commentarymentioning
confidence: 99%
“…42,57 Guidelines stipulate that patients need to be equipped not only with an emergency card but also with an emergency kit for parenteral glucocorticoid self-administration. 83 A recent survey 89 performed in Germany on 33 patients showed that less than 70% carried an emergency kit, almost 80% were unable to correctly adjust the glucocorticoid dose during common illnesses and only 20% could identify the symptoms of over- and undertreatment.…”
Section: Standard Glucocorticoid Therapymentioning
confidence: 99%
“…2,88 Its potency stems from the inadequate level of cortisol that is unable to modulate the immune response, thus favoring the inflammatory cytokines excess, and to enhance vascular reactivity to catecholamines. 2,89 Other precipitators are surgical procedures, physical or psychological stress, or abrupt interruption of corticosteroid replacement. 2,88 As for risk factors, patients with PAI are much more prone because of the deficit of mineralocorticoid hormones.…”
Section: Acute Stress Managementmentioning
confidence: 99%
“…Knowledge about "sick-day" rules, the importance of "steroid cards," and the utility of parenteral steroids is shown to be suboptimal. 14,15…”
Section: Introductionmentioning
confidence: 99%